(untitled) (RIAF. International Journal of Physical Activity, 2026)
This study focuses on institutional certification for personal trainers in Angola as an alternative for professionalization in the promotion and well-being of physical and mental health. It has a mixed qualitative-quantitative and descriptive-propositional approach, using surveys, interviews, and documentary analysis. The results reveal regulatory gaps and training deficiencies in the training of professionals specializing in personal training. The sustained growth of the fitness and physical activity sector in Angola has generated a growing demand for personal trainers in recent years, without a formal professional accreditation system to guarantee the certification, quality, safety, and effectiveness of the services offered. The absence of recognized institutional certification limits the professionalization of the sector and reduces its potential contribution to public health policies, in a context where chronic noncommunicable diseases represent a national health challenge. Likewise, it was found that there is no specific law regulating professional certification in the field of fitness, which supports the need for a technical and institutional framework to guarantee the quality and safety of the practice. An alternative for professional advancement is proposed, comprising a comprehensive institutional certification model that combines academic training, technical evaluation, and legal recognition of personal trainers, in coordination with the Ministry of Youth and Sports and the Ministry of Health at the national level. This proposal seeks to promote ethics and professional technical competence, and to integrate fitness practice into national legal strategies for preventive public health and social welfare.